Ads Avoidance And Attitude Towards Online Advertising Among Net-Generation In Jakarta - Henilia YULITA; Pinckey TRIPUTRA; Udi RUSADI; Titi WIDANIGSIH (International Journal of Environmental, Sustainability, and Social Science, 2022)
Advertising is a form of non-personal presentation consisting of promoting ideas, goods, and services by certain sponsors and being paid. However, the trend of ad blocker users continues to increase and is expected to penetrate mobile devices. With this ad blocker, the advertisements carried out by the brand will not be able to reach the intended target market. This study examines factors influencing the Internet generation's avoidance of advertising on social media. This type of research is quantitative, taking all net-generation in Jakarta as the population and 490 net-generation as a sample. Sampling in this study is non-probability sampling. The results of this study indicate that the attitude towards online advertising is directly and significantly influenced by the variables of entertainment, informativeness, credibility, personalization, and incentives. In contrast, the irritation variable has no effect. The advertising avoidance variable is also directly and significantly influenced by the attitude towards online advertising and irritation. However, it is not influenced by entertainment, Informativeness, credibility, Personalization, and incentive variables. Meanwhile, advertising avoidance is influenced indirectly and significantly by the variables of entertainment, Informativeness, credibility, Personalization, and incentives through the attitude towards online advertising as a moderating variable. At the same time, the advertising avoidance variable is not affected indirectly and significantly by the irritation variable through the attitude towards online advertising as a moderating variable.